Bitcoin: A New Asset Class? - Rr. Widad Nawa Huwaida; Taofik Hidajat (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
This study aims to examine the effect of stock prices, exchange rates, and gold prices on the Bitcoin price. The data used are the IDX Composite, the Rupiah/ IDR exchange rate, and the daily gold price from July 19, 2010, to December 31, 2018. Regression equation results show that stock prices, exchange rates, and the gold price had a positive effect on Bitcoin price. Changes will follow changes that occur in stock prices, exchange rates, and gold prices in the price of Bitcoin in the same direction. Bitcoin is considered the same as other assets that are worth having in the investment portfolio.